Edu-Agri: Oppurtunity for Support the Education and Increases Food Security in Hanoi, Vietnam and Northern Sumatera, Indonesia - Ameilia Zuliyanti Siregar; Novizar; Ravindra C. Joshi (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2026)
This study explores the potential of educational agricultural tourism (edu-agri-tourism) through rice field landscapes in Sapa-Hanoi, Vietnam, and Medan, Indonesia. The research highlights how traditional rice farming systems, particularly the terraced paddy fields in Sapa and the highland rice fields on the outskirts of Medan, function as valuable cultural assets and educational tourism destinations. Using a comparative qualitative approach, the study examines local knowledge, eco-tourism practices, and youth motivation in both regions. Sapa’s terraced rice fields demonstrate well-developed tourism programs that successfully combine ethnic traditions with sustainable agricultural practices. In contrast, Medan possesses strong natural potential but still lacks effective integration between its agricultural resources and tourism sector. The findings underline the importance of participatory planning, community capacity building, and the development of eco-services to enhance food security, educational opportunities, and sustainable tourism experiences through rice field tourism in both areas.